2015
DOI: 10.1007/s12161-015-0309-1
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Methods Applied to Characterization of Actinidia arguta, Actinidia deliciosa, and Actinidia eriantha Kiwi Fruit Cultivars

Abstract: In this research, eight kiwi fruit genotypes (six hardy kiwis (Actinidia arguta and their hybrids), one of Actinidia deliciosa 'Hayward,' and one of Actinidia eriantha 'Bidan' were examined and compared by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), Fourier transform infrared (FT-IR) spectra, and nuclear magnetic resonance (NMR) spectroscopy. Proteins were extracted from lyophilized fruits, flesh with seeds, grinded seeds, and singular seeds and then separated by SDS-PAGE. Matrix simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…The Anova significance (male parent, female parent and male 9 female) for all compounds at P value \ 0.001 'Weiki' and 'Geneva' with A. arguta males 'Rubi', 'Nostino' and 'Joker'. This finding can be explained by the high biochemical similarity between A. arguta genotypes used for crossing (Drzewiecki et al 2016). On the other hand, when A. arguta females were crossed with 'Rot' and 'Tomuri' males we could reveal up to three new bands in the protein spectrum.…”
Section: Influence Of Different Pollen Sources On the Protein Composition Of Seedsmentioning
confidence: 94%
See 2 more Smart Citations
“…The Anova significance (male parent, female parent and male 9 female) for all compounds at P value \ 0.001 'Weiki' and 'Geneva' with A. arguta males 'Rubi', 'Nostino' and 'Joker'. This finding can be explained by the high biochemical similarity between A. arguta genotypes used for crossing (Drzewiecki et al 2016). On the other hand, when A. arguta females were crossed with 'Rot' and 'Tomuri' males we could reveal up to three new bands in the protein spectrum.…”
Section: Influence Of Different Pollen Sources On the Protein Composition Of Seedsmentioning
confidence: 94%
“…The seed protein pattern is recognized as the most suitable approach for distinguishing and identifying crop cultivars (Cooke 1989;Konarev et al 2001). In the case of kiwifruit and other Actinidia species, protein patterns consist of low and middle molecular peptides units in the range of 14-45 kDa (Miraghaee et al 2011;Maddumage et al 2013;Drzewiecki et al 2016). Our previous study revealed that it is difficult to distinguish A. arguta cultivars on the basis of seed protein pattern (Drzewiecki et al 2016).…”
Section: Influence Of Different Pollen Sources On the Protein Composition Of Seedsmentioning
confidence: 96%
See 1 more Smart Citation
“…'Kuilv' fruits are smaller than traditional kiwifruit such as 'Hayward' but have a superb flavour and hairless, edible skin, making them convenient to eat (Williams et al, 2003). Moreover, in terms of cultivation, 'Kuilv' can withstand multiple stresses, such as low temperatures of up to −30 • C and pests and diseases, which can reduce the planting costs (Drzewiecki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Actinidia genus includes 66 species, but only four are cultivated for fruit production. Of these, A. deliciosa and A. chinensis are the most accepted by consumers worldwide [58,59]. Here, we will refer to both species indistinctly.…”
Section: Kiwifruit (Actinidia Deliciosa [A Chev] Cf Liang Et Ar Fementioning
confidence: 99%